Dietary effect of Alstonia Boonei stem bark extract on hematological profiles of Wistar albino rats after inducing oxidative stress with CCl4 - Robert I., Uroko; Victor E., Okpashi; Bayim P.R., Bayim; Anthony U., Onwuekwe; Kate M., Ucho; Igori, Wallace (African Science Publications, 2020)
This study examined the dietary outcome of Alstonia boonei stem bark. A. boonei stem bark was extracted with ethanol after air-drying and grinding. Hematological indices of Wistar albino rats were impacted with carbon tetrachloride (CCl4). Eighteen male albino mice were used to check acute toxicity of the extract while 30 albino rats were used to examine the hematological functions – Packed cell volume (PCV), hemoglobin (Hb) concentration, total white blood cell (WBC) count, total red blood cell (RBC) count and platelet count. The rats were separated into six sets of five rats each. Set-1 stands for normal control, and 2 ml/kg body weight of distilled water was given to them. Set- 2 to 6 rats were induced with CCl4, though set-2 was untreated, it represents negative control while set-3 was treated with Silymarin drug and represents positive control. Set- 4 to 6 rats were given 100, 200 and 500 mg/kg body weight of A. boonei extract for 14 days. The acute toxicity study of A. boonei extract showed greater safeties as no death was recorded after 24h. After giving classified doses of A. boonei extract, a non-significant (p > 0.05) increase in albumin concentration was observed which proposes no toxic effect, an indication that the extract may have protective properties for hepatocytes. It was warned that the extract may be toxic to bile function since there was a significant (p < 0.05) increase in total bilirubin for all the sets that were given A. boonei stem bark extract. The no significant (p > 0.05) decrease in PCV count, also suggests a marked loss of red blood cells. The no significant (p > 0.05) increase in hemoglobin concentration recommended that a low concentration of the extract was not toxic to hemoglobin concentration. The non-significant (p > 0.05) increase in WBC and RBC count in rats—given a low dose of A. boonei extract show that at low concentration, the extract may exercise antibody effect. The non-significant (p > 0.05) decrease in platelet concentration in all the sets given A. boonei extract compared to the normal control (set-1) might offer homeostatic properties or decreased platelet production due to A. boonei stem bark extract. The findings advocate that A. boonei stem bark if consumed, may protect hepatic cells due to its potentials against assault from intoxicants.
Keywords: A. boonei, Hematology, CCL4, Oxidative stress, Nutrition and antioxidant